Analysis of Artificial Intelligence Assisted Proof Process Through Principle of Mathematical Induction in Real Analysis Course - Isnawati Lujeng Lestari; Mayang Sari; Gusti Uripno; Siti Suprihatiningsih; Firda Hariyanti; Ebenezer Bonyah (Universitas Negeri Surabaya, 2025)
The low proficiency of Mathematics Education students in constructing mathematical proofs, especially using the principle of mathematical induction, highlights the need for enhanced learning approaches. One promising method is the integration of Artificial Intelligence (AI) into the proof process within Real Analysis courses. This study aims to describe how students carry out mathematical induction proofs with the assistance of AI. Ten voluntary students enrolled in Real Analysis participated in an initial test involving divisibility problem. From this group, two students were selected through maximum variation sampling based on their answer diversity and communication skills. One student employed a modulo-based approach, while the other used the divisibility-definition concept. Overall, the results demonstrate that AI significantly supports students in understanding problems, planning proofs, implementing strategies, and revising their reasoning. AI played a critical role in concept generation, solution evaluation, and embedded reflection across each stage of Polya’s problem-solving framework, combined with the three aspects of AI-assisted proof: construction, evaluation, and revision